Analysis and control of inverter operation in microgrids - Peng, Xiaoyang (2017)
This thesis conducts analyses, and proposes and investigates inverter operation control system on several different AC and DC microgrids. The coordination and control of the inverter operation in microgrids are crucial to integrate different renewable energy in power systems. This thesis digs into different problems occur in the microgrid to accommodate multiple inverters while sustaining the stability and reliability of the system. Firstly, a centralized control strategy within an energy management system (EMS) are proposed for an AC based microgrid consists of PV, battery, fuel cell and microturbine. For this inverter-interfaced AC microgrid, parallel operation of all the inverters during both grid-connected and islanded operations is realized through a coordination control in the EMS with two different model predictive control (MPC) based control modes for inverters: current control mode (CCM) and voltage control mode (VCM). Several case studies are carried out through simulations with detailed analysis, and they validate that the proposed centralized control strategy can handle different operations. Secondly, the system frequency analysis of the islanded condition of an inverter-interfaced AC microgrid is conducted. A combined centralized and decentralized control strategy is proposed using MPC based inverter control. A frequency model is incorporated in the EMS for coordination control among different distributed generation (DG) units. To test scenarios are studied through simulations. These simulations illustrate the frequency problems and prove that the proposed combined centralized and decentralized control strategy can handle different conditions in islanded condition. Finally, the analysis and study of inverter operation and control extend to DC based microgrids to investigate harness the excess wind energy in poultry farms. A double-inverter configuration between DC bus and AC bus in the DC based microgrid is proposed. A double-mode MPC algorithm (VCM and CCM) and a control strategy in the EMS is proposed to handle the two inverters’ operation. Several simulation tests are analyzed, and they prove the effectiveness of the control algorithm and the double-inverter operation principle.